Riscrivere la storia. Modalità di rappresentazione del colonialismo italiano in Albania - Comberiati, Daniele (Incontri. Rivista europea di studi italiani, 2013)
Departing from the contemporary work of migrant authors of Albanian origin − OrnelaVorpsi, Anilda Ibrahimi and Elvira Dones − as well as from the theatrical monologueItalianesi by Saverio La Ruina, this article delves into the question of identity within postcolonial discourse. What role, in fact, do the Italian colonizers that remainedbehind in the liberated colonies play? How does their ‘hybrid’ identity help us toreflect upon colonial violence and upon the difficulties the colonizers themselves would have experienced internally when faced with accepting this violence? Additionally, the specific discussion of Albania, vis-à-vis narratives of contemporary migrants, allows us to reflect upon the Italian situation in particular, which, from unification to the present day offers specific material for the discussion of the relationship to, and the confronting of, the theme of ‘otherness’. A broad definition of ‘European’ colonialism − that goes beyond the alleged African otherness and runs along the same lines as a redefinition vehemently proposed by new groups of migrants in Italy (in particular by those from the Albanian immigration wave of 1991)− allows one to question the Italian ambitions in regards to the Balkans and the Eastern expansion across national borders.